1980
DOI: 10.1007/bf00342348
|View full text |Cite
|
Sign up to set email alerts
|

Somatosensible Leitungsmessungen bei neurologischen Systemerkrankungen

Abstract: Twenty-eight patients with peroneal muscular atrophy (PMA) have been investigated. Eighteen of them were affected by the Charcot-Marie-Tooth disease and three by Dejerine-Sottas disease. In these 21 cases the nerve conduction velocity (NCV) was decreased. Four patients presented the neuronal type of PMA, two cases showed sensory neuropathy of the neuronal type with ophthalmoplegia, and one case, PMA with ataxia, i.e., a myatrophic ataxia. In the neuronal type of PMA, including both cases with ophthalmophegia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Noel and Desmedt [29] reported that none of their 6 or more patients had a significant delay to the onset of the first cortical negative peak. O n the other hand, 22 patients reported by Jones et a1 [21] and 17 reported by Sauer [38] all had N 2 0 latency delays. Of another 8 cases studied by Mastaglia et a1 [25], half had N 2 0 latency delays.…”
Section: Auditory Testingmentioning
confidence: 87%
“…Noel and Desmedt [29] reported that none of their 6 or more patients had a significant delay to the onset of the first cortical negative peak. O n the other hand, 22 patients reported by Jones et a1 [21] and 17 reported by Sauer [38] all had N 2 0 latency delays. Of another 8 cases studied by Mastaglia et a1 [25], half had N 2 0 latency delays.…”
Section: Auditory Testingmentioning
confidence: 87%